A mitochondria-targeting fluorescent probe for the selective detection of glutathione in living cells. Issue 5 (6th January 2017) - Liu, Xue-Liang; Niu, Li-Ya; Chen, Yu-Zhe; Zheng, Mei-Ling; Yang, Yunxu; Yang, Qing-Zheng
Abstract : We report a fluorescent probe for the selective detection of mitochondrial glutathione (GSH). Abstract : We report a fluorescent probe for the selective detection of mitochondrial glutathione (GSH). The probe, containing triphenylphosphine as a mitochondrial targeting group, exhibited ratiometric and selective detection of GSH over Cys/Hcy. The probe was used for imaging mitochondrial GSH in living HeLa cells.